Rekayasa Ulang Proses Deteksi Dini Penyakit Tidak Menular Pada Puskesmas Bangkalan - Az-Zahra, Feisyah; Suharso, Wildan (STIKOM Tunas Bangsa Pematangsiantar, 2025)
Non-Communicable Diseases (NCDs) are chronic diseases that develop slowly, are not transmitted between humans or animals, and usually show no symptoms in their early stages. Prevention efforts through early detection of NCDs can be carried out in health facilities such as community health centers (Puskesmas). Puskesmas Bangkalan plays a crucial role in the examination of NCDs. However, the current process has several shortcomings in terms of time, cost, service, and resources. This study aims to improve the efficiency of the early detection process of NCDs at Puskesmas Bangkalan through the approach of Business Process Reengineering (BPR). The methods used include data collection, business process analysis, throughput efficiency testing, and solution implementation. The results of the study indicate that the application of BPR can increase the throughput efficiency of the patient registration process and physical activity examination from 66.67% and 64.28% to 100% respectively. The recommendations from this process resulted in a web-based interface design to enhance process efficiency.